Relationships among satisfaction, treatment motivation, and expectations in orthodontic patients: a prospective cohort study - Li W; Wang S; Zhang Y (Patient Preference and Adherence, 2016)
Weihong Li, Shimei Wang, Yanzhen Zhang The Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, People’s Republic of China Background: Few research projects have looked at patient satisfaction with treatment outcome and factors contributing to satisfaction. The aim of this study was to examine treatment motivation and expectation associated with treatment-outcome satisfaction in a group of adolescent nonextraction orthodontic patients. We hypothesized that there would be significant correlations among treatment-outcome satisfaction, motivation, and expectations.Subjects and methods: A sample of 120 patients who received orthodontic treatment at the Second Affiliated Hospital of Zhejiang University School of Medicine completed two questionnaires. Before treatment, questionnaire 1 was given to patients to assess treatment motivation and expectations. When treatment had been completed, questionnaire 2, concerning treatment satisfaction, was assessed. Spearman’s rank correlation and regression analyses were used to assess the relationships among treatment satisfaction, expectations, and motivation.Results: A total of 110 patients completed the two questionnaires. There was a tendency toward significant correlations between treatment motivation and overall satisfaction with treatment (β-coefficient –0.264, 95% confidence interval –0.456 to 2.314; P<0.001). However, correlations among treatment motivation and satisfaction with changes made and satisfaction with one’s appearance posttreatment were more fragmented. No relationship between treatment expectation and satisfaction was found (β-coefficient –0.126; 95% confidence interval –0.024 to 0.524; P>0.05).Conclusion: Motivation was correlated with satisfaction with treatment outcome. Patients’ expectations had no correlation with treatment satisfaction. Keywords: motivation, orthodontic treatment, expectation, treatment-outcome satisfaction